An approach towards sustainable coastal tourism management : nature-based tourism in Nuup Kangerlua, Greenland - Hildur Sólveig Elvarsdóttir 1985- (2013)
Verkefnið er lokað til 23.5.2014. This thesis discusses the opportunities and challenges associated with nature-based tourism in Nuup Kangerlua, Greenland. Nuup Kangerlua is a complex fjord system that is home to Nuuk, the capital of Greenland, and Kapisillit, a small village inst in the fjord. The fjord is mostly wilderness where hunting, fishing, recreation activities, tourism, transport, and perhaps soon to be iron ore mining take place. The wilderness offers opportunities for increased tourism development. Such development opportunities can cause both positive and negative impacts on the environment, society and the economy. Three key concepts introduced in this thesis for sustainable nature-based coastal tourism development in Nuup Kangerlua include sustainable coastal tourism management, nature-based tourism, and the Broker-Local-Tourist (BLT) model. Three assessments were conducted for Nuup Kangerlua and served as the tools needed in order to develop and manage sustainable tourism. The BLT assessment showed that the actors of the tourism sector in Nuup Kangerlua have a close relationship; most tourists either visit family or are in Nuuk on business. The natural amenity and facility assessment showed that Nuup Kangerlua has many nature-based amenities although the facilities for nature-based tourism activities are modest and should be developed and marketed to meet the tourism needs. The conflict assessment showed that conflicts within the tourism sector, as well as growing conflicts with other coastal sectors, were present. As a result of the assessments, it is recommended to increase tourism marketing in Nuuk. In order to increase the number of tourism sites visited and increase the number of tourists, it is recommended that recreation areas be identified and labeled. Planning for a marine protected area and biosphere reserve should also be commenced. To reduce conflict within the tourism sector and between coastal sectors, it is recommended that nature guidelines and integrated coastal zone management ...